2012
DOI: 10.12659/msm.882448
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of metabolic syndrome in elderly Japanese-Brazilians

Abstract: SummaryBackgroundPrevalence of individuals with a high cardiovascular risk is elevated in elderly populations. Although metabolic syndrome (MS) increases cardiovascular risk, information is scarce on the prevalence of MS in the elderly. In this study we assessed MS prevalence in a population of elderly Japanese-Brazilians using different MS definitions according to waist circumference cutoff values.Material/MethodsWe studied 339 elderly subjects, 44.8% males, aged between 60 to 88 years (70.1±6.8). MS was defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…Korean survey of cardiometabolic syndrome reported that there was an increasing trend of metabolic syndrome with elevating ages and with the highest rate among subjects older than 60 years (37.9%) [1]. Similarly, results from the SABE survey claimed that the prevalence of MetS was 66.0% in elderly women and 47.1% in elderly men which was closed to many previous studies [2][3][4]. Previous studies already con rmed that MetS were relatively more prevalent among urban residents when compared with rural residents [5,6].…”
Section: Introductionmentioning
confidence: 76%
“…Korean survey of cardiometabolic syndrome reported that there was an increasing trend of metabolic syndrome with elevating ages and with the highest rate among subjects older than 60 years (37.9%) [1]. Similarly, results from the SABE survey claimed that the prevalence of MetS was 66.0% in elderly women and 47.1% in elderly men which was closed to many previous studies [2][3][4]. Previous studies already con rmed that MetS were relatively more prevalent among urban residents when compared with rural residents [5,6].…”
Section: Introductionmentioning
confidence: 76%
“…In elderly Japanese-Brazilians the MetS prevalence ranged from 59.9% to 65.8% according to the different definitions. The prevalence of altered MetS components was as follows: arterial blood pressure 82%, fasting glycaemia 65.8%, triglycerides 43.4%, and HDL-C levels 36.9% [25].…”
Section: Research Articlementioning
confidence: 99%
“…A Korean cardiometabolic syndrome survey reported an increasing case of metabolic syndrome with an increase in age, with the highest rate among subjects older than 60 (37.9%) ( 2 ). The National Survey of Health, Wellbeing, and Aging survey also showed that the prevalence of MetS was 66.0% in older women and 47.1% in older men ( 3 5 ) and is relatively more prevalent among urban than rural residents ( 6 , 7 ). However, data from our study indicated that the prevalence of MetS among general rural residents was 39.0%, which was significantly higher than many other rural Chinese areas, such as Hanzhong (15.1%), Nantong (23.3%), and Xinjiang (14.43%) ( 8 10 ).…”
Section: Introductionmentioning
confidence: 99%